Autonomous Weapons Systems and International Norms - Bode, Ingvild (Montreal and kingston: London: Chicago: McGill-Queen's University Press, 2022)
"Ingvild Bode and Hendrik Huelss present a study of how testing, developing, and using weapons systems with autonomous features shapes ethical and legal norms, and how standards manifest and change in practice. Autonomous weapons systems are not a matter for the distant future: some autonomous features, such as in air defense systems, have been in use for decades. They have already incrementally changed use-of-force norms by setting emerging standards for what counts as meaningful human control. As United Nations discussions drag on with minimal progress, the trend towards autonomizing weapons systems continues. This book provides an analysis of the normative repercussions of weaponizing artificial intelligence"
Cover -- AUTONOMOUS WEAPONS SYSTEMS AND INTERNATIONAL NORMS -- Title -- Copyright -- Contents -- Tables and figures -- Acknowledgements -- Abbreviations -- Introduction -- 1 Autonomous Weapons Systems and International Relations -- 2 New Technologies of Warfare: Emergence and Regulation -- 3 International Law, Norms, and Order -- 4 Norms in International Relations -- 5 How Autonomous Weapons Systems Make Norms -- Conclusion -- Notes -- References -- Index
Keywords: Autonomous weapons systems; Autonomous weapons systems -- Moral and ethical aspects; Air defense system; Artificial intelligence -- Military applications